The abundance of a farmland specialist bird, the skylark, in three European regions with contrasting agricultural management - Koleček, J. (Jaroslav); Reif, J.; Weidinger, K. (Agriculture, Ecosystems & Environment, 2015)
Advances in our understanding of recent farmland biodiversity loss have mainly come from studies in Western Europe. The application of such findings to other regions is questionable, however, and limits the outcomes of management actions. To bridge this knowledge gap, we focused on relationships between farmland bird abundance and sward height and crop type, counting breeding birds in three Central European regions with different agricultural histories and practices: the Eastern Czech Republic, Western Germany and Central Poland. We used the skylark (Alauda arvensis) as a model species due to its tight association with open habitats year-round and its commonness in European farmland. Skylarks were more abundant in Poland than in Germany and the Czech Republic, probably due to less intensive farmland management. Mean abundance declined with growing sward height from April to June and slightly declined with the number of fields surrounding study sites in all regions. Autumn- and spring-sown cereals hosted the highest abundance of skylarks in May, with lower abundance in maize, oilseed rape and meadows irrespective of region. This variation in skylark numbers suggests a temporal shift in abundance, probably reflecting movement between crops with optimal sward height. Taken together, these results indicate that skylark habitat use is somewhat conserved over regions and this knowledge can be used in management plans throughout Europe. However, the observed differences in skylark abundance between regions suggest that the regional-specific level of agricultural intensity may affect the delivery of conservation benefits from such plans.